2016
DOI: 10.1016/j.heliyon.2016.e00200
|View full text |Cite
|
Sign up to set email alerts
|

Morningness-eveningness in a large sample of German adolescents and adults

Abstract: People differ in their sleep-wake behavior. This individual difference is conceptualized in different aspects, such as wake up times, bed times, times of peak performance, as well as in morning affect. A total of 14,987 visitors of an exhibition in the LWL State Museum of Natural History, Münster (Germany), did the survey on chronotype and gave their consent that these data can be used for a scientific study. Age groups were coded into 5-year bins. Mean age (mean ± SD) was 28.2 ± 17.5 years. There were 8075 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 40 publications
(77 reference statements)
7
24
0
6
Order By: Relevance
“…: N = 14,650; from ≈20 to >60 years12; Italy: Tonetti et al . : N = 8,972, 10–87 years13; Germany: Randler et al ., N = 14,987; 5–70 years14). …”
mentioning
confidence: 99%
“…: N = 14,650; from ≈20 to >60 years12; Italy: Tonetti et al . : N = 8,972, 10–87 years13; Germany: Randler et al ., N = 14,987; 5–70 years14). …”
mentioning
confidence: 99%
“…While the progressive tendency toward eveningness as a function of age was confirmed in almost all of the previous studies, findings on sex differences are less consistent (4,(25)(26)(27). A higher eveningness preference is found in adolescent girls, although in some studies, differences in the circadian preferences with regard to sex were not found.…”
Section: Discussionmentioning
confidence: 80%
“…Dok je progresivna tendencija večernjosti u funkciji dobi potvrđena gotovo u svim dosadašnjim istraživanjima, nalazi o razlikama s obzirom na spol manje su konzistentni (4,(25)(26)(27). Najčešće se veća sklonost večernjosti utvrđuje u adolescentica, premda u nekim istraži-vanjima nisu dobivene razlike u cirkadiurnim preferencijama s obzirom na spol.…”
Section: Discussionunclassified
See 2 more Smart Citations